2020
DOI: 10.1186/s12870-020-02641-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between genetics and environment shape Camelina seed oil composition

Abstract: Background Camelina sativa (gold-of-pleasure) is a traditional European oilseed crop and emerging biofuel source with high levels of desirable fatty acids. A twentieth century germplasm bottleneck depleted genetic diversity in the crop, leading to recent interest in using wild relatives for crop improvement. However, little is known about seed oil content and genetic diversity in wild Camelina species. Results We used gas chromatography, environmental niche assessment, and genotyping-by-sequencing to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 63 publications
5
26
0
9
Order By: Relevance
“…Camelina is no exception. Recently, Brock et al (2020) demonstrated that seed oil content and FA composition significantly differ among Camelina species and can substantially differ within the species due to growth conditions, especially temperature. Temperature greatly affects FA synthesis (Singer et al, 2016), and it is common for seed storage lipids to increase in unsaturation under low temperatures and display greater saturation under high temperatures (Linder, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Camelina is no exception. Recently, Brock et al (2020) demonstrated that seed oil content and FA composition significantly differ among Camelina species and can substantially differ within the species due to growth conditions, especially temperature. Temperature greatly affects FA synthesis (Singer et al, 2016), and it is common for seed storage lipids to increase in unsaturation under low temperatures and display greater saturation under high temperatures (Linder, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we conclude that Andrzejowski originally collected specimens of C. microcarpa somewhere in the eastern part of the presentday Moldova or adjacent parts of Ukraine (probably Odessa Region), along the left (eastern) bank of the Dnister [Nistru in Moldovan/Romanian, also Dniester] River between Camenca town and the confluence of the Dnister and Yagorlyk [Iagorlîc] rivers, most probably on limestone outcrops because plants typical for the whole "limestone area" in Andrzejowski's lists in that chapter were marked by asterisks. This suggests that the type of C. microcarpa probably belongs to the southern Ukrainian populations, which are genetically different from northern and central Ukrainian ones (Brock et al, 2020).…”
Section: Holotypusmentioning
confidence: 92%
“…A traditional European oilseed crop Camelina sativa (L.) Crantz (Brassicaceae) is becoming increasingly popular as an emerging biofuel source (Vollmann & Eynck, 2015;Blume & Rakhmetov, 2017;Brock et al, 2018Brock et al, , 2020Guittet et al, 2018;etc.). Taxa of the genus Camelina Crantz also served as classical models for important early studies of microevolution, crop origins, and co-evolution of crops and their specialized weeds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations